Rural-urban interaction in Tuva (based on interviews with natives of the Ovyursky District) - Tarbastaeva, Inna S. (The New Research of Tuva, 2024)
The article analyzes the characteristics of rural-urban interactions in the Republic of Tuva. The study was based on semi-structured in-depth interviews conducted in Ovyursky District in 2022 with rural and urban residents, as well as former rural residents who have now become urban residents.One of the key features of rural-urban relations in Tuvan society is their intensity, which is reflected in the density of interactions between rural and urban inhabitants. Drawing on D. K. Lynch's concept of rural-urban flows, the author identified several main types: economic food transfers from rural areas to cities, seasonal labor migration from cities to villages, educational transfers of schoolchildren from villages to cities, and ethnocultural exchanges from cities to rural areas. Dense informal economic interaction occurs primarily due to the maintenance of a shared shepherd's parking lot. There is an exchange of food and labor between relatives who participate in this activity. In Tuvan villages, the practice of sending children to urban schools with relatives is common, leading to overcrowding in urban education institutions. In turn, rural areas provide an important spiritual component for city dwellers, giving them a sense of sacredness and a place where they can preserve the Tuvan language and culture.The author argues that due to rural-urban interactions, residents are attempting to overcome socioeconomic challenges and compensate for the lack of social benefits and institutional support.
Keywords: Tuva; Tuvans; Kyzyl; Ovyur; rural-urban; shepherd's camp; food; relatives; dagylga